Respostas

  • Usuário do Brainly
2013-11-28T15:43:13-02:00
Adotando: an = 3 + 2n + n^2
dados:
a1 = ?
a2 = ?
a3 = ?
a4 = ?

substitua:

a1 = 3 + 2*1 + 1^2
a1 = 3 + 2 + 1
a1 = 6

a2 = 3 + 2*2 + 2^2
a2 = 3 + 4 + 4
a2 = 11

a3 = 3 + 2*3 + 3^2
a3 = 3 + 6 + 9
a3 = 18

a4 = 3 + 2*4 + 4^2
a4 = 3 + 8 + 16
a4 = 27
3 2 3
2013-11-28T16:19:08-02:00
Seja an=3+2n+n²
temos:
a1= 3+2*1+1² =3+2+1=6

a2= 3+2*2+2² =3+4+4= 11

a3= 3+2*3+3² =3+6+9= 18

a4= 3+2*4+4² =3+8+16= 27

portanto os 4 primeiros termos da sequencia são {6,11,18,27}
1 5 1